An in vitro model for cyclosporin A-induced interference of intrathymic clonal elimination (The Rockefeller University Press, 1990)
The effects of cyclosporin A (CsA) on influencing the intrathymic clonal deletion were investigated by using our established thymic stromal cell clone with capacities to express Ia antigens and to produce a unique T cell growth factor. The following were revealed: (a) T cell clone with a given specificity was killed on the Ia+ stromal cell monolayer in the presence of the relevant antigens, a process depending on T cell receptor (TCR) stimulation; and (b) CsA allowed the T cell clone to continuously proliferate even during TCR stimulation by virtue of the stromal cell-derived T cell growth factor. This paper describes an in vitro model of a mechanism by which CsA is responsible for the generation of normally "forbidden" T cell clones.